2012
DOI: 10.1016/s0968-8080(12)40680-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural barriers to screening for and treatment of cervical cancer in Peru

Abstract: Through in-depth interviews with 30 key informants from 19 institutions in the health care system in four regions of Peru, this study identifies multiple barriers to obtaining cervical cancer screening, follow-up, and treatment. Some facilities outside Lima do not have the capacity to take Pap smear samples; others cannot do so on a continuing basis. Variation in procedures used by facilities and between regions, differences in women’s ability to pay, as well as varying levels of training of laboratory personn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 14 publications
(16 reference statements)
3
62
0
10
Order By: Relevance
“…[11,12] A study consisting of a series of interviews conducted with 30 healthcare professionals across institutions in several regions of Peru found that two major structural barriers to effective screening were the widespread lack of resources and the centralization of cervical cancer treatment and cytology services in the capital, and revealed that women could access screening but not easily obtain treatment. [13] Historically, El Salvador has had the lowest reported cervical cancer screening coverage (19%) among all Latin American countries, [8] with the Pap smear the most common method of screening. Alternatives to the Pap smear, such as visual inspection with acetic acid (VIA) and HPV-DNA testing, are gaining acceptability in El Salvador; however, cytology remains the most widely used screening method.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] A study consisting of a series of interviews conducted with 30 healthcare professionals across institutions in several regions of Peru found that two major structural barriers to effective screening were the widespread lack of resources and the centralization of cervical cancer treatment and cytology services in the capital, and revealed that women could access screening but not easily obtain treatment. [13] Historically, El Salvador has had the lowest reported cervical cancer screening coverage (19%) among all Latin American countries, [8] with the Pap smear the most common method of screening. Alternatives to the Pap smear, such as visual inspection with acetic acid (VIA) and HPV-DNA testing, are gaining acceptability in El Salvador; however, cytology remains the most widely used screening method.…”
Section: Introductionmentioning
confidence: 99%
“…Estos resultados coinciden con estudios nacionales en Manchay (Lima) e Iquitos donde se reporta una preferencia por la autotoma de 81,4% e incomodidad y dolor con la autotoma de 11,6% (7) . De esta manera, se presenta un avance en afrontar barreras para el tamizaje de cáncer cervical como el tiempo de espera dentro del centro de salud, la incomodidad y la vergüenza al momento del examen pélvico (18)(19)(20) . Las líderes comunitarias refirieron que, cuando la ofrecían, algunas mujeres desconfiaban de la prueba por la inseguridad de que sea autoadministrada correctamente, esta es una duda que ha persistido, como se evidencia en las razones para preferir la toma en el centro de salud.…”
Section: Discussionunclassified
“…(45) PHC participants' knowledge grades regarding cancer cervix and overall knowledge were significantly better among physicians who heard about Pap smear and those who attended CME on cervical cancer and its screening. In addition, participants' overall knowledge grades about cancer cervix were significantly better among physicians who ask asymptomatic patients about cancer cervix screening and those who had their information from online sources.…”
mentioning
confidence: 90%